Spin-1 Haldane Phase in a Chain of Rydberg Atoms - J. Mögerle; K. Brechtelsbauer; A.T. Gea-Caballero; J. Prior; G. Emperauger; G. Bornet; C. Chen; T. Lahaye; A. Browaeys; H.P. Büchler (PRX Quantum)
We present a protocol to implement a spin-1 chain in Rydberg systems using three Rydberg states close to a Förster resonance. In addition to dipole-dipole interactions, strong van der Waals interactions naturally appear due to the presence of the Förster resonance and give rise to a highly tunable Hamiltonian. The resulting phase diagram is studied using the infinite density-matrix renormalization group and reveals a highly robust Haldane phase—a prime example of a symmetry-protected topological phase. We find experimentally accessible parameters to probe the Haldane phase in current Rydberg systems, and demonstrate an efficient adiabatic preparation scheme. This paves the way to probe the remarkable properties of spin fractionalization in the Haldane phase.